Стихотворения/Осип Мандельштам - Мандельштам Осип Эмильевич (Азбука-классика, 2016)
Экземпляры: абонемент (15.10.2020) / Инвентарный номер: 51233 / Цена: 111,41 / Сис.шифр: 84(2Роc=Рус)6 / Авт.знак: М 23 / ГРНТИ: 17.82.10 / ББК: 84(2Рос-Рус)6-5